Contemporary atheism and method to deal with it: A study on its understanding among the phenomenon of universities’ students in Amman, Jordan / Main Sayel Friawan Alsaleh - Main Sayel Friawan , Alsaleh (2019)
In this study, the researcher approaches an important issue, it is a statement of the atheism concept, its contemporary manifestations, the analysis of its causes, the most important spreading methods, the impacts on the individual, the family and society, the treatment methods must be considered to confront this belief defect, and individuals’ understanding level of the contemporary manifestations of atheism and its effects on the individual, family and society in addition the treatment methods based on practical approach. The study aims to identify the most important causes of atheism and its effects on Arab and Islamic societies and address the belief defect that has spread in our student community, it has also aimed to protect young people from the atheistic ideas by increase awareness level of its causes and contemporary manifestations and establish the best methods to approach and confront it. The inductive method and the historical approach in addition to the descriptive analytical approach have been applied carefully. The questionnaire has been used to support the study with specific data and figures. A random sample of students from Amman universities was selected in Jordan. To sum up, the most important findings indicate that students at the universities of Amman have a low understanding level of the contemporary manifestations of atheism and average understanding level of the atheism impacts on Arab and Islamic societies. The study has demonstrated that there is statistically significant differences in the level of significance(a0.05≥) between the average scores of the sample (students) for their understanding of the atheism concept, the main reasons, and treatment techniques considering the following “The atheism’s manifestations, the atheism’s causes, the atheism’s effects, the techniques of treatment”. Such these differences results from considering the academic qualification factor. In addition, the study has confirmed that there is no considerable relationship associated to the gender factor.